Intravascular Lithotripsy in Calcified Coronary Lesions: A Single-Center Experience in “Real-World” Patients - Mastrangelo, Angelo; Monizzi, Giovanni; Galli, Stefano; Grancini, Luca; Ferrari, Cristina; Olivares, Paolo; Chiesa, Mattia; Calligaris, Giuseppe; Fabbiocchi, Franco; Montorsi, Piero; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To describe the outcome of intravascular lithotripsy (IVL) when used with different indications and to assess the short- and long-term outcomes of IVL-facilitated PCI. Background: IVL can improve the results of percutaneous coronary intervention (PCI) of calcified coronary lesions with low rate of peri-procedural complications. Methods: One hundred five consecutive patients with 110 calcified lesions underwent IVL. Eighty-seven de novo lesions were treated by IVL with the following indications: 25 before attempting other balloon-based devices (primary IVL), 51 after failure of non-compliant balloon dilatation (secondary IVL), and 11 after stent implantation because of stent under-expansion (bailout IVL). In 23 lesions, IVL was used for the treatment of in-stent restenosis (ISR). Effectiveness (angiographic success) and safety (major adverse cardiovascular events [MACE] and IVL-related procedural complications) endpoints were assessed. Results: Angiographic success was achieved in 84.6% lesions. Early MACE were peri-procedural MI only, ranging from 6.7% to 20% depending on MI definition. Flow-limiting dissections rate was 2.7%. Five (4.5%) IVL balloons ruptured during treatment with subsequent vessel perforation in 1 case. MACE at 12 months were 13.3%, with TLR occurring in 8 lesions (12% primary IVL, 0% secondary IVL, 0% bailout IVL, and 21.7% IVL for ISR, p = 0.002). Conclusions: Treatment of calcified coronary lesions with IVL in a “real-world” setting can be performed with high success, low rate of procedural complications and an acceptable MACE rate. Target lesion failure may be more frequent when IVL is performed for the treatment of peri-procedural ISR due to calcium-mediated stent under-expansion.